Evaluation of potentially toxic elements and ecological risks associated with environmental liabilities in Tacna, Peru - César Julio Cáceda Quiroz; Gisela July Maraza Choque; Gabriela de Lourdes Fora Quispe; Diana Galeska Farfan Pajuelo; Edwin Denis Obando Velarde; Fulvia Chiampo; Milena Carpio Mamani (PLoS ONE, 2025)
Mining environmental liabilities (MELs) are abandoned deposits resulting from extractive activities that pose a high risk of contamination and remain an unresolved challenge for authorities worldwide. This study evaluated the contamination levels of potentially toxic elements (PTEs) and their associated ecological risks in MELs, using multiple environmental indices. Analyses were performed following the EPA 6020A method with acid digestion and inductively coupled plasma mass spectrometry (ICP-MS), while free cyanide and hexavalent chromium were determined using the EPA 9013A and EPA 7199 methods, respectively. The results revealed elevated concentrations of arsenic (1,102 mg/kg), cadmium (271 mg/kg), lead (15,961 mg/kg), and free cyanide (64 mg/kg), which exceeded regulatory standards by a considerable margin. Statistically significant differences were observed across the sites (p < 0.05). In addition, the presence of flora, fauna, rivers, and rural communities in proximity to these abandoned mining sites amplifies both ecological and social risks. The applied indices consistently indicated severe levels of contamination and high ecological risk across all areas evaluated. Although no statistically significant differences were found in some indices (p > 0.05), the magnitude of the recorded values remains ecologically relevant. Notably, each index has its own interpretative scale, allowing for an independent and robust evaluation of contamination severity and its potential ecological implications. Principal Component Analysis (PCA) revealed multiple sources of pollution, while Spearman correlation analysis identified strong associations among PTEs, suggesting common environmental dispersion pathways. This research provides a critical preliminary assessment of the risks associated with these environmental legacies and emphasizes the urgent need for remediation efforts at both local and global scales. The current lack of action is largely attributed to the absence of comprehensive baseline assessments. The findings underscore the importance of prioritizing their management through sustainable strategies and international policies to mitigate environmental impacts.